Accumulated oxygen deficits among highly conditioned female rowers during a 2,000-meter race simulation - Pripstein, L. P.; Coutts, K. (Medicine & Science in Sports & Exercise, 1997)
Highly trained female rowers (N = 16) performed two activities on a Concept II rowing ergometer: (a) 4 x 4-min submaximal and one 2-min maximal performance, and (b) a 2 K race simulation. VO2 and power outputs were very highly correlated in each rower. The estimated accumulated oxygen deficit averaged 3.40 liters while the actual deficit on the race simulation was 3.50. There was no statistical difference between these values. Implication. In a 2 K race simulation on a rowing ergometer, highly trained females tax their anaerobic capacities maximally and anaerobic work constitutes 13% of the energy demands of the effort. This value is lower than the 19% reported for men by Hagerman (1984). Women rowers should predominantly emphasize aerobic conditioning in their rowing training.